2007
DOI: 10.2353/ajpath.2007.061093
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamic, Inflammatory, and Apoptotic Responses to Lipopolysaccharide in HO-1−/− Mice

Abstract: ؉/؉ mice. We conclude that HO-1 deficiency exhibits a heightened and dysregulated inflammatory response to LPS accompanied by greater impairment in renal hemodynamic response and widespread apoptosis of immune cells. Because polymorphisms in the HO-1 gene with diminished HO activity predispose to human disease, we speculate that our findings may be relevant to the clinical outcome in patients with sepsis syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 59 publications
3
64
0
Order By: Relevance
“…35,36 Interestingly, both HO-1 as well as the product of its activity, CO, have been shown to inhibit activation of the NF-B pathway, [37][38][39] and CO has been shown to inhibit polyclonal T-cell proliferation in response to anti-CD3 and anti-CD28. 40 It is therefore possible that the induction of HO-1 during the early steps of DC activation may aid in the acquisition of a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Interestingly, both HO-1 as well as the product of its activity, CO, have been shown to inhibit activation of the NF-B pathway, [37][38][39] and CO has been shown to inhibit polyclonal T-cell proliferation in response to anti-CD3 and anti-CD28. 40 It is therefore possible that the induction of HO-1 during the early steps of DC activation may aid in the acquisition of a tolerogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…25,26) These studies suggest that HO-1 plays an important role in reducing the deleterious increase in oxidative damage. Srisook et al reported that both O 2 − and NO are related to HO-1 induction in macrophages by using an O 2 − generator and a NO donor.…”
Section: )mentioning
confidence: 99%
“…[25][26][27][28][29] Colonies of mice were maintained by breeding HO-1 Ϫ/Ϫ males with HO-1 ϩ/Ϫ females. Offspring were genotyped at the time of weaning using PCR to amplify the wild-type and mutant alleles of genomic DNA from tail samples.…”
Section: Methodsmentioning
confidence: 99%